(untitled) (Bangladesh Journal of Child Health, 2024)
Background: Autism spectrum disorder (ASD) is lifelong neurodevelopmental disorder characterized by impairments in social function, communication, and certain behaviors. The etiology of ASD is unclear & it is believed to be multi-factorial, among those several prenatal & perinatal factors are found to be significant. So, the necessity of this study is to detect the presence of known risk factors of ASD which in turn may help in the early diagnosis and intervention for better long-term outcomes. Objective: To find out prenatal and perinatal risk factors of ASD. Method: A case control study was conducted with 112 cases of ASD and 201 controls of 2-6 years of age. The study was carried out in Center for Neurodevelopment and Autism in Children (CNAC), in the department of Paediatrics, Bangabandhu Sheikh Mujib Medical University and Autism Welfare Foundation (AWF). ASD was diagnosed by DSM-IV TR criteria. Mothers were interviewed and data were collected by semistructured questionnaires. Results: Total 5 risk factors were identified as the risk factors of ASD. They were: advanced paternal age (OR=2.84) and maternal age (OR=1.87); male baby (OR=2.01); environmental stress during pregnancy (OR=1.61) and preterm delivery (OR=1.80). Conclusions: It is concluded that advanced paternal age, maternal age, male baby, environmental stress during pregnancy and preterm delivery are associated with increased risk of ASD. BANGLADESH J CHILD HEALTH 2022; VOL 46 (3) : 115-121